2011
DOI: 10.1016/j.lfs.2011.09.004
|View full text |Cite
|
Sign up to set email alerts
|

Reactive oxygen and nitrogen species modulate the ex-vivo effects of LPS on platelet adhesion to fibrinogen

Abstract: Our findings suggest that in LPS-treated rats, NO plays an important modulatory role only in non-stimulated platelet adhesion through cGMP-independent mechanisms, while ROS, directly or by affecting the redox state of the animals, modulates both non-activated and thrombin-activated platelet adhesion.

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1
1

Citation Types

1
3
0
1

Year Published

2013
2013
2021
2021

Publication Types

Select...
7

Relationship

1
6

Authors

Journals

citations
Cited by 8 publications
(7 citation statements)
references
References 50 publications
1
3
0
1
Order By: Relevance
“…4). This finding agrees with the reports of lack of effect of LPS [21] and TNFa [22] in platelets isolated from mice, though others have observed spontaneous platelet activation upon LPS stimulation [23]. We note that these conflicting studies were conducted with platelets from species other than mice, suggesting that interspecies differences may be involved in the different responses.…”
Section: Effect Of Ascorbate On Plasminogen Activator Inhibitor-1 Prosupporting
confidence: 91%
“…4). This finding agrees with the reports of lack of effect of LPS [21] and TNFa [22] in platelets isolated from mice, though others have observed spontaneous platelet activation upon LPS stimulation [23]. We note that these conflicting studies were conducted with platelets from species other than mice, suggesting that interspecies differences may be involved in the different responses.…”
Section: Effect Of Ascorbate On Plasminogen Activator Inhibitor-1 Prosupporting
confidence: 91%
“…Blood platelet activation plays a critical role in LPS-induced thrombocytopenia and tissue damage. Activated platelets produce ROS that cause damage of the vascular endothelium and promote multiple organ dysfunctions in sepsis (Casarin et al 2011, Tyml 2011. Some studies showed that LPS stimulates platelet secretion of dense and alpha granules, and release of biological active inflammatory mediators (Zhang et al 2009).…”
Section: Platelets Contribution In Inflammatory Processesmentioning
confidence: 99%
“…Lipopolysaccharide (LPS) from the cell envelope of Gram-negative bacteria is a principal cause of the symptoms of sepsis and this can result in platelet sequestration in the lungs and liver, thrombocytopenia and disseminated intravascular coagulation (DIC) [ 2 , 3 ]. LPS has been reported to modulate the function of platelets [ 4 , 5 , 6 ], although the underlying mechanisms of LPS action remain unclear. Indeed, some studies have indicated that exposure of platelets to LPS in vitro potentiates platelet function [ 7 , 8 ], while others have indicated that it supresses their activity [ 9 ].…”
Section: Introductionmentioning
confidence: 99%